Land of the Dinosaurs - Roderick Hunt (Oxford Reading Tree, 2012)
The children are making dinosaur models when the magic begins again. Level 6, Stories Copyright © Reading Chest 2025. This book is called Land of the Dinosaurs. It's published by Oxford Reading Tree, and has a book band of Orange. It's part of our Reading Chest library of books to rent.